Management of Coronary Artery Spasm - Gaetano Antonio Lanza; Hiroaki Shimokawa (European Cardiology Review)
Calcium channel blockers (CCBs) are the first-line treatment for coronary artery spasm (CAS). When CAS-related angina symptoms are not well controlled by CCB therapy, long-acting nitrates or (where available) nicorandil can be added as second-line medications. In the case of CAS refractory to standard treatments, several other alternative drugs and interventions have been proposed, including the Rho-kinase inhibitor fasudil, anti-adrenergic drugs, neural therapies and percutaneous coronary interventions. In patients with syncope or cardiac arrest caused by CAS-related tachyarrhythmias, or even bradyarrhythmias, implantation of an ICD or pacemaker, respectively, should be considered according to the risk of recurrence and efficacy of vasodilator therapy.